Towards a Common Language for Mainstreaming Nature-Based Solutions Through Coastal Systems in the North Sea Region: The Manabas Coast Project - Geert J. M. van der Meulen; Jurre J. de Vries; Lisa van Well; Frances A. Kannekens (Journal of Marine Science and Engineering, 2025)
Nature-based solutions (NBSs) offer an opportunity to address environmental and societal challenges worldwide while simultaneously providing benefits for human well-being as well as biodiversity. Despite a growing demand and evidence base for NBSs in coastal systems, the scaling of their implementation and mainstreaming of their principles in policy and practice are constrained by multiple barriers, such as misinterpretations of concepts, effectiveness, or locked-in preferences or conventions of traditional solutions. To address these constraints, an international consortium of coastal authorities and experts in the North Sea Region collaborates to validate, document, and share learnings of NBSs to establish a framework for mainstreaming NBSs for flood and coastal erosion risk management around the North Sea. Co-creation processes of workshops, field visits, and expert knowledge sessions contributed to a theoretical framework and baseline assessments of exemplary sandy and muddy case study sites in the region, amongst others, iteratively providing and showcasing building blocks for the mainstreaming framework. This article takes stock halfway of the project’s activities, learnings, and status of the called-for common language.